2023
DOI: 10.34133/energymatadv.0039
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal MBenes-Supported Single Atom as Electrocatalysts for the Nitrogen Reduction Reaction

Abstract: The electrocatalytic nitrogen reduction reaction (NRR) is currently constrained by sluggish reaction kinetics and poor selectivity because of the difficulties in activating inert N≡N triple bonds and the existence of competing hydrogen evolution reaction (HER). Therefore, electrocatalysts with high activity, selectivity, and stability are highly desired. Herein, by means of first-principles calculations, we investigated the electrocatalytic NRR performance of a series of transition metal atoms (e.g., 3d, 4d, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…All calculations were performed using the spin-polarized density functional theory (DFT) method based on the projector augmented wave (PAW) approach, as implemented in the Vienna Ab inito Simulation Package (VASP). , The exchange–correlation energy was modeled using the Perdew–Burke–Ernzerhof (PBE) functional within the generalized gradient approximation (GGA) framework. This choice was made based on the proven accuracy of the PBE functional in calculating Gibbs free energy . An energy cutoff of 550 eV was used for the plane-wave basis set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All calculations were performed using the spin-polarized density functional theory (DFT) method based on the projector augmented wave (PAW) approach, as implemented in the Vienna Ab inito Simulation Package (VASP). , The exchange–correlation energy was modeled using the Perdew–Burke–Ernzerhof (PBE) functional within the generalized gradient approximation (GGA) framework. This choice was made based on the proven accuracy of the PBE functional in calculating Gibbs free energy . An energy cutoff of 550 eV was used for the plane-wave basis set.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been demonstrated that MoC 2, Mo 2 B 2 , and Fe 2 B 2 exhibit outstanding electrochemical properties. Additionally, MBenes serve as an ideal matrix for supporting signal-atom catalysts. , However, research on MBenes in the field of electrochemistry is still in its early stages , and has primarily focused on orthorhombic MAB. , Moreover, although theoretical calculations show that MBenes have a great potential in electrochemical catalysis, how to obtain MBenes from their parent material MAB phases remains a great challenge …”
Section: Introductionmentioning
confidence: 99%
“…29,36 However, the discovery of h-MBenes is still limited, and currently only four h-MBenes (ZrB, HfB, TiB, and Hf 2 B) have been theoretically identified as promising candidates for applications in metal-ion batteries and electrocatalysis with transition-metal modifications. [17][18][19]24,3037 These initial successful studies have inspired researchers to further explore the intrinsic properties and potential applications of h-MBenes in more depth.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the ternary laminate transitional metal borides (MAB phases), which are analogous to MAX phases, due to their potential for selective etching into 2D counterparts known as MBenes. Among these, 2D orthorhombic transition-metal borides ( ort -MBenes) have emerged as promising candidates for applications in Li-ion batteries (LIB) electrodes and electrocatalysis materials since 2017, leading to a growing emphasis on the experimental and theoretical investigation of MBenes in energy storage, magnetic devices, and catalysts. However, the selective etching of A layers from orthorhombic MAB ( ort -MAB) phases poses challenges. Currently, only two ort -MAB phases, MoAlB and Cr 2 AlB 2 , have been investigated as precursors for the synthesis of ort -MBenes (MoB and CrB). , In 2019, our research group successfully predicted and synthesized the first hexagonal ternary laminate MAB ( h -MAB) phase, Ti 2 InB 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation